BEASISWA BIDIKMISI TERHADAP PENCAPAIAN IPK SEBAGAI KINERJA MAHASISWA PROGRAM STUDI S1 ADMINISTRASI PUBLIK FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO - Aini Muniroh; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2020)
Education is an essential aspect for the economic growth in Indonesia. However, in its application, education in Indonesia is still low because many school aged children cannot continue their education due to tuition reason. Therefore, the government provides scholarship for every level of education as the form of help. For example at the level of higher education. At this level, the government provides Bidikmisi scholarship for underprivileged students who want to continue their education. With the Bidikmisi scholarship, students are expected fulfil the target that is determined by government. One of the targets that must be achieved is having minimum GPA of 3.00 as the form of students’ performance during their study. This study aims to discover whether Bidikmisi scholarship can encourage the achievement of the Public Administration undergraduate program, FISIP, UNDIP students’ GPA as the students’ performance or not. The method of this study is explanatory method with questioner and interview as the data collecting method. The population of this study is the entire students who receive Bidikmisi scholarship in Public Administration batch 2016, 2017, and 2018. The samples chosen are 51 respondents with probability sampling as the sampling technique. The data analysis used is validity test, reliability test, simple regression analysis, coefficient of determination, and significance test (t test) using SPSS. According to the result of the study, Bidikmisi scholarship has impact toward students’ performance as the effort to achieve GPA. It is known from the coefficient of determination calculation of 28.3%. Bidikmisi scholarship is proven having positive and significant effect toward students’ performance that is proven with the calculation result of 4.392. According to the study result, the writer suggests that students must be more enthusiastic in achieving their GPA as the form of students’ performance. Students are expected to understand the benefit of the competitions held and be enthusiastic to participate in those competitions.